1998
DOI: 10.1038/sj.onc.1202250
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric repeats on small polydisperse circular DNA (spcDNA) and genomic instability

Abstract: Small polydisperse circular DNA (spcDNA) is a heterogeneous population of extrachromosomal circular molecules present in a large variety of eukaryotic cells. Elevated amounts of total spcDNA are related to endogenous and induced genomic instability in rodent and human cells. We suggested spcDNA as a novel marker for genomic instability, and speculated that spcDNA might serve as a mutator. In this study, we examine the presence of telomeric sequences on spcDNA. We report for the first time the appearance of tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 18 publications
2
67
1
Order By: Relevance
“…Recently, we have demonstrated that the minicircles replicate via a rolling-circle mechanism which generates tandem arrays of the telomeric sequence that may recombine with linear molecules of mtDNA to lengthen the telomeres (L. Tomaska, A. M. Makhov, J. D. Griffith & J. Nosek, unpublished). This may parallel alternative mechanisms of nuclear telomere maintenance involving telomeric small polydisperse circular DNAs detected in several telomerasenegative tumour cell lines (Regev et al, 1998) and Xenopus oocytes (Cohen & Mechali, 2002), or an elongation of telomeres by recombination with DNA circles as demonstrated in the yeast Kluyveromyces lactis (Natarajan & McEachern, 2002).…”
Section: Evolutionary Implicationsmentioning
confidence: 99%
“…Recently, we have demonstrated that the minicircles replicate via a rolling-circle mechanism which generates tandem arrays of the telomeric sequence that may recombine with linear molecules of mtDNA to lengthen the telomeres (L. Tomaska, A. M. Makhov, J. D. Griffith & J. Nosek, unpublished). This may parallel alternative mechanisms of nuclear telomere maintenance involving telomeric small polydisperse circular DNAs detected in several telomerasenegative tumour cell lines (Regev et al, 1998) and Xenopus oocytes (Cohen & Mechali, 2002), or an elongation of telomeres by recombination with DNA circles as demonstrated in the yeast Kluyveromyces lactis (Natarajan & McEachern, 2002).…”
Section: Evolutionary Implicationsmentioning
confidence: 99%
“…In Candida parapsilosis and other yeast species with linear mitochondrial DNA, rolling circles may be used for maintaining the mitochrondrial DNA termini (Tomaska et al, 2000). Telomere repeat circles have been found in human tumors and in a human immortal cell line (Regev et al, 1998). Other types of small circular DNA have been found in human cells and are considered to be either a marker or an enhancer of genomic instability (Cohen et al, 1997;Wahl, 1989).…”
Section: Rolling Circlementioning
confidence: 99%
“…Taken together, the results suggest that the APBs contain DNA structures recognized by DNA damage checkpoint proteins, and a fraction of them induce the localization of ␥-H2AX. (41)(42)(43). Therefore, it is important to know if telomeric DNAs at APBs detected by FISH and TRF1-staining are derived from native telomeres or extrachromosomal telomeric DNAs.…”
Section: Table I Percentages Of Cells With Hrad9 Nuclear Foci And/or mentioning
confidence: 99%